PENGARUH PENYULUHAN MENGGUNAKAN MODEL PHANTOM GIGI TERHADAP STATUS KEBERSIHAN GIGI DAN MULUT PADA SISWA KELAS 3 - Putri, Winda Gusnizar; Putri, Megananda Hiranya; Widyastuti, Tri (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2024)
School-age children are at risk of experiencing oral health problems. Efforts that can be made to prevent dental diseases in school-age children include brushing teeth. Dental cleanliness after brushing can be measured using the O'Leary Plaque Index. However, appropriate oral health education materials are needed to teach proper brushing techniques, including the use of dental phantoms. The purpose of this study is to determine the effectiveness of counseling using a dental phantom on the oral hygiene status of third-grade students at SDN 018 Sukagalih in Bandung City. This research method uses a pre-test design with a one-group pre-test design. The results of the study showed a reduction in dental plaque before and after receiving counseling using a dental phantom. It can be concluded that there is an effect of counseling using a dental phantom on oral hygiene status with a significant value of p = 0.000 (p < 0.05).